RESPON PEMERINTAH INDONESIA TERHADAP HAK ASASI ANAK DALAM KONVENSI INTERNASIONAL - Rahman, Abdul (JPP (Jurnal Politik Profetik), 2015)
Children’s rights are well-established through various international conventions. But, international conventions do not well implemented in Indonesian law. Besides that, international convention is often interpreted differently in Indonesian law. To guarantee children’s rights, the government and society of Indonesia must be effort to implement international conventions already ratified correctly.